APLIKASI PENGOLAHAN DATA KEUANGAN PADA PT. EPSINDO JAYA PRATAMA PRABUMULIH BERBASIS WEB - Fersa Julian Toni; Khana Wijaya; Ahmad Barnianto (Elkom : Jurnal Elektronika dan Komputer, 2024)
PT. Epsindo Jaya Pratama is a company engaged in manufacturing. This research contains web- based financial informasi processing applications, because they can help make it easier to work on. The problems that occurred at PT. Epsindo Jaya Pratama is currently still conventional or still manual, that is, it still uses the Ms. Excel. This study aims to help make it easier to input financial informasi for PT. Epsindo Jaya Pratama, by submitting suggestions for creating a web- based financial informasi processing application, it is hoped that later financial informasi processing will be easier, faster and more practical. In this financial informasi processing application, it is proposed to use the Xampp program with PHP and MySQL databases which will make workmanship easier in processing financial reports.